Does night work affect age at which menopause occurs?. Issue 6 (December 2019) - Stock, David; Schernhammer, Eva
Abstract : Purpose of review: To delineate the current state of evidence on the impact of night shift work on age at natural menopause. Recent findings: The only direct evidence is from a single observational study, which indicates that women who work night shifts are at moderately higher risk for earlier menopause and that this risk is more pronounced among younger women. Underlying biological mechanisms have yet to be sufficiently substantiated. A long-held line of inquiry, most strongly propagated by the observed link between night shift work and female breast cancer, is the 'Light at Night' hypothesis, which suggests melatonin-mediated circadian disruption as a potential regulator of reproductive signaling in women. Supporting evidence is found from observations of changes in endogenous melatonin production among night working women or in response to light exposure, and corresponding changes in endogenous ovarian hormone levels and modulated menstrual patterns, among other indications of altered central ovulation-governing processes. Susceptibility to night shift work may be modified by chronotype. Summary: This review summarizes the literature related to night work and ovulatory regulation in humans, prioritizing population-based evidence to provide motivation for the study of circadian disruption and night shift work as a regulator of menopausal timing.